2017
DOI: 10.1089/apc.2016.0299
|View full text |Cite
|
Sign up to set email alerts
|

The Strategies of Heterosexuals from Large Metropolitan Areas for Assessing the Risks of Exposure to HIV or Other Sexually Transmitted Infections from Partners Met Online

Abstract: Heterosexuals' use of the Internet for meeting romantic or sexual partners is rapidly increasing, raising concerns about the Internet's potential to facilitate encounters that place individuals at risk for acquiring HIV or other sexually transmitted infections (STIs). For example, online sharing of personal information and self-revelations can foster virtual intimacy, promoting a false sense of familiarity that might accelerate progression to unprotected sex. Therefore, it is critical to understand how those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…The extant literature examining individuals' own HIV risk appraisals indicates that the relationship between perceived and actual risk is complex, and that perceived risk is only weakly associated with what is classified as actual risk according to epidemiological correlates (Gerrard, Gibbons, & Bushman, 1996;Holtzman, Bland, Lansky, & Mack, 2001;Kesler et al, 2016;Klein, Elifson, & Sterk, 2003;Klepinger, Billy, Tanfer, & Grady, 1993;Koh & Yong, 2014;Maurier & Northcott, 2000;Mayer et al, 2012;Prata, Morris, Mazive, Vahidnia, & Stehr, 2006;Siegel, Lekas, Onaga, Verni, & Gunn, 2017). Of particular note is that in many cases, the main element used by individuals in assessing risk is the perceived personal characteristics of their sexual partner.…”
Section: Introductionmentioning
confidence: 99%
“…The extant literature examining individuals' own HIV risk appraisals indicates that the relationship between perceived and actual risk is complex, and that perceived risk is only weakly associated with what is classified as actual risk according to epidemiological correlates (Gerrard, Gibbons, & Bushman, 1996;Holtzman, Bland, Lansky, & Mack, 2001;Kesler et al, 2016;Klein, Elifson, & Sterk, 2003;Klepinger, Billy, Tanfer, & Grady, 1993;Koh & Yong, 2014;Maurier & Northcott, 2000;Mayer et al, 2012;Prata, Morris, Mazive, Vahidnia, & Stehr, 2006;Siegel, Lekas, Onaga, Verni, & Gunn, 2017). Of particular note is that in many cases, the main element used by individuals in assessing risk is the perceived personal characteristics of their sexual partner.…”
Section: Introductionmentioning
confidence: 99%
“…We found that heterosexual men and those from neighbourhoods with higher socioeconomic deprivation were less likely to return their sampling kits. As these are populations at risk of STI and HIV, 19 increasing the return rate of sampling kits from these populations is a priority for our service. However, based on the data available from the surveys, we were not able to hypothesise as to why these groups were less likely to return their samples and, as such, are not able to propose changes to the service to improve sample return.…”
Section: Discussionmentioning
confidence: 99%
“…A complete description of the recruitment and screening procedures has been published in a report of a different aim of this study. 44 The data analyzed for this report come for the in-depth interviews. One of the study aims was to investigate how relationships developed online and progressed to meeting offline, to sexual contact, and eventually to unprotected sex.…”
Section: Recruitment and Data Collectionmentioning
confidence: 99%